Neoadjuvant Bevacizumab Plus Docetaxel/Cisplatin/Capecitabine Chemotherapy in Locally Advanced Gastric Cancer Patients: A Pilot Study - Yu, Deguo; Wang, Zhenfeng; He, Tingbang; Yang, Lijun (Frontiers in Surgery, 2022)
Background: Bevacizumab (BEV) plus chemotherapy as neoadjuvant regimen presents good efficacy in locally advanced cancer patients. However, its role in locally advanced gastric cancer (LAGC) patients is not clear. Thus, the study aimed to assess the efficacy and safety of neoadjuvant BEV plus chemotherapy in LAGC patients. Methods: Twenty resectable LAGC patients who received BEV plus docetaxel/cisplatin/capecitabine (DCC) chemotherapy for 3 cycles with 21 days as one cycle as neoadjuvant regimen were involved. Besides, their treatment response, survival profiles and adverse events were assessed. Results: Two (10.0%), 9 (45.0%), 8 (40.0%) and 1 (5.0%) patients achieved complete remission, partial remission, stable disease and progressive disease (PD) according to imaging evaluation, which resulted in 55.0% of objective response rate and 95.0% of disease control rate, respectively. Moreover, the number of patients with pathological response grade 1, 2 and 3 was 8 (40.0%), 8 (40.0%) and 3 (15.0%); while 1 (5.0%) patient did not receive surgery due to PD, thus the data of this patient was not assessable. Meanwhile, 18 (90.0%) patients achieved R0 resection. Regarding survival profile, the median disease-free survival or overall survival were both not reached. The 1-year, 2-year and 3-year disease-free survival rates were 88.8%, 80.7% and 67.3%. Meanwhile, the 1-year, 2-year and 3-year overall survival rates were 100.0%, 75.8% and 75.8%, respectively. Additionally, the main adverse events were anemia (90.0%), alopecia (90.0%), leukopenia (70.0%) and anorexia (65.0%). Indeed, most adverse events were of grade 1 or 2 and were manageable. Conclusion: Neoadjuvant BEV plus DCC chemotherapy presents favorable pathological response and survival profile with acceptable safety in LAGC patients.